Protective Signature of IFNγ-Stimulated Microglia Relies on miR-124-3p Regulation From the Secretome Released by Mutant APP Swedish Neuronal Cells - Gonçalo Garcia; Gonçalo Garcia; Adelaide Fernandes; Adelaide Fernandes; Frank Stein; Dora Brites (Frontiers Media S.A., 2022)
Microglia-associated inflammation and miRNA dysregulation are key players in Alzheimer's disease (AD) pathophysiology. Previously, we showed miR-124 upregulation in APP Swedish SH-SY5Y (SWE) and PSEN1 iPSC-derived neurons and its propagation by the secretome (soluble and exosomal fractions). After modulation with miR-124 mimic/inhibitor, we identified common responsive mechanisms between such models. We also reported miR-124 colocalization with microglia in AD patient hippocampi. Herein, we determined how miR-124 modulation in SWE cells influences microglia polarized subtypes in the context of inflammation. We used a coculture system without cell-to-cell contact formed by miR-124 modulated SWE cells and human CHME3 microglia stimulated with interferon-gamma (IFNγ-MG), in which we assessed their adopted gene/miRNA profile and proteomic signature. The increase of miR-124 in SWE cells/secretome (soluble and exosomal) was mimicked in IFNγ-MG. Treatment of SWE cells with the miR-124 inhibitor led to RAGE overexpression and loss of neuronal viability, while the mimic caused RAGE/HMGB1 downregulation and prevented mitochondria membrane potential loss. When accessing the paracrine effects on microglia, SWE miR-124 inhibitor favored their IFNγ-induced inflammatory signature (upregulated RAGE/HMGB1/iNOS/IL-1β; downregulated IL-10/ARG-1), while the mimic reduced microglia activation (downregulated TNF-α/iNOS) and deactivated extracellular MMP-2/MMP-9 levels. Microglia proteomics identified 113 responsive proteins to SWE miR-124 levels, including a subgroup of 17 proteins involved in immune function/inflammation and/or miR-124 targets. A total of 72 proteins were downregulated (e.g., MAP2K6) and 21 upregulated (e.g., PAWR) by the mimic, while the inhibitor also upregulated 21 proteins and downregulated 17 (e.g., TGFB1, PAWR, and EFEMP1). Other targets were associated with neurodevelopmental mechanisms, synaptic function, and vesicular trafficking. To examine the source of miR-124 variations in microglia, we silenced the RNase III endonuclease Dicer1 to block miRNA canonical biogenesis. Despite this suppression, the coculture with SWE cells/exosomes still raised microglial miR-124 levels, evidencing miR-124 transfer from neurons to microglia. This study is pioneer in elucidating that neuronal miR-124 reshapes microglia plasticity and in revealing the relevance of neuronal survival in mechanisms underlying inflammation in AD-associated neurodegeneration. These novel insights pave the way for the application of miRNA-based neuropharmacological strategies in AD whenever miRNA dysregulated levels are identified during patient stratification.